Ontology learning and population techniques for English extended quranic translation text - Saidah Saad, 1971-, author 567247 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Thesis (Doktor Falsafah, Bidang Penyelidikan: Sains Komputer)) - Universiti Teknologi Malaysia, 2014